2021
DOI: 10.1101/2021.02.09.21251402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Whole-genome sequencing of SARS-CoV-2 in the Republic of Ireland during waves 1 and 2 of the pandemic

Abstract: Background: Whole-genome sequencing (WGS) of SARS-CoV-2 laboratory-confirmed cases can provide insights into viral transmission and genetic diversity at a population level. However, less is known about the impact of non-pharmaceutical interventions (NPIs), including lockdowns, on circulating SARS-CoV-2 lineages and variants of concern, the relative contribution of travel to re-emergence of pandemic waves within communities or how different lineages and variants contribute to disease severity. Methods: We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Our estimation for the 1st July is 2.1% (95% CI: 1.2-3.6%) and is in complete accordance with a survey study that shows a sero-prevalence of 1.7% (95% CI: 1.1-2.4%) between 22nd June and 16th July 2020 [19]. Figure 4 displays our estimation of the time evolution of the sero-prevalence that shows a large increase from the beginning of January 2020 due to the high propagation of the UK variant [15,16] but, also, it would seem, due to the rolling out of the vaccination.…”
Section: T) (B) Infected Non Infectious E(t) = E 1 (T) + E 2 (T) C Symptomatic Infectious I(t) = I 1 (T) + I 2 (T) D Asymptomatic Infectisupporting
confidence: 86%
“…Our estimation for the 1st July is 2.1% (95% CI: 1.2-3.6%) and is in complete accordance with a survey study that shows a sero-prevalence of 1.7% (95% CI: 1.1-2.4%) between 22nd June and 16th July 2020 [19]. Figure 4 displays our estimation of the time evolution of the sero-prevalence that shows a large increase from the beginning of January 2020 due to the high propagation of the UK variant [15,16] but, also, it would seem, due to the rolling out of the vaccination.…”
Section: T) (B) Infected Non Infectious E(t) = E 1 (T) + E 2 (T) C Symptomatic Infectious I(t) = I 1 (T) + I 2 (T) D Asymptomatic Infectisupporting
confidence: 86%
“…Similar studies have been reported from a plethora of countries around the world including the UK, Ireland, Russia, India, Qatar etc. [26,[33][34][35][36]. These studies provide valuable information on the routes of importation of new strains and the emergence of critical mutations that change key parameters such as transmissibility or virulence, as was recently highlighted by the discovery of the B.1.617 variant and its B.1.617.2 sub-lineage in India [37], which led to a surge of SARS-CoV-2 infections in Delhi.…”
Section: Resultsmentioning
confidence: 97%
“…The B.1.177 lineage, which is characterized by the A222V spike mutation, was previously been shown to have emerged in Spain in early summer and subsequently became widespread across Europe as well as Canada, accounting for the majority of sequences by autumn 2020 [25,26]. However, no evidence of increased transmissibility of this variant was reported [27].…”
Section: Resultsmentioning
confidence: 99%
“…The B.1.177 lineage, which is characterized by the A222V spike mutation, was previously been shown to have emerged in Spain in early summer and subsequently became widespread across Europe as well as Canada, accounting for the majority of sequences by autumn 2020 [16,17]. However, no evidence of increased transmissibility of this variant was reported [18].…”
Section: Resultsmentioning
confidence: 99%